Does research performance explain the "leaky pipeline" in Indian academia? A study of agricultural and applied economics. (9th October 2022) - Bansal, Sangeeta; Viswanathan, Brinda; Meenakshi, J. V.
Abstract: This article documents the existence of a leaky pipeline based on complete enumeration of faculty in two large public academic networks: state agricultural universities and institutions of the Indian Council of Social Science Research. We then examine if there are gender differences in the quantity and quality of research publications of women relative to men that can explain this. As proxies for quality and visibility, we use several metrics, including the number of citations, h‐index, i10 index, and Scimago rank of the journal in which the research is featured. A novel aspect of the analysis is the comparison of time paths of cumulative publications over career paths of men and women professors. Our analysis of research performance is based on scraping publicly‐available data sources, including faculty and institutional websites, and google scholar pages, and represents one‐third (and likely positively selected) of all faculty in these institutions. Our results suggest that women are disadvantaged in terms of number of publications during early career years, however, the disadvantage is mitigated with seniority and women perform equally well or even surpass men later in their careers. Women are more likely to write single‐authored articles and have fewer collaborators than men, indicating that they do not access collaborative spaces as much, and are less networked than men. In spite of this, there is suggestive evidence that women are more quality conscious than men. This nuanced look at research productivity suggests the source of the leaky pipeline does not arise from differences in performance.